Detection of aedes aegypti mosquitoes infected with dengue virus as a complementary method for increasing the sensitivity of surveillance: identification of serotypes 1, 2, and 4 by rt-pcr in Quintana Roo, Mexico - Méndez Galván, Jorge Fernando; Sánchez Casas, Rosa María; Gaitan Burns, Alejandro; Díaz González, Esteban Eduardo; Ibarra Juárez, Luis Arturo; Medina de la Garza, Carlos Eduardo; Domínguez Galera, Marco Antonio; Mis Ávila, Pedro; Fernández Salas, Ildefonso (Society of Southwestern Entomologists, 2014)
Abstract. Sensitivity of monitoring Aedes aegypti (L.) populations was determined to identify the distribution of dengue virus (DENV) during epidemics in Quintana Roo. From September to November 2012, we used a motorized aspirator to collect 2,144 female Ae. aegypti from 569 homes. These were grouped into 220 to use semi-nested RT-PCR for DENV, and positive groups were analyzed individually. Five groups (2.27%) were positive for DENV. Individual analysis yielded eight groups that tested positive, six with DENV-2, one DENV-1, and one DENV-4. The latter was not reported by the surveillance system that year. The mean number of female mosquitoes per household was 3.77 ± 5.71, and the rate of viral infection of Ae. aegypti was 0.4%. Most infected mosquitoes (49%) were concentrated in 10% of the houses. Monitoring Ae. aegypti infected with DENV has the potential to complement the current system of clinical and entomological surveillance.